2004
DOI: 10.1126/science.1092805
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Secondary Organic Aerosols Through Photooxidation of Isoprene

Abstract: Detailed organic analysis of natural aerosols from the Amazonian rain forest showed considerable quantities of previously unobserved polar organic compounds, which were identified as a mixture of two diastereoisomeric 2-methyltetrols: 2-methylthreitol and 2-methylerythritol. These polyols, which have the isoprene skeleton, can be explained by OH radical-initiated photooxidation of isoprene. They have low vapor pressure, allowing them to condense onto preexisting particles. It is estimated that photooxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,157
3
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,389 publications
(1,238 citation statements)
references
References 26 publications
40
1,157
3
9
Order By: Relevance
“…These results support that oxalic, malonic, and succinic acids as well as phthalic and glyoxylic acids are produced by the photochemical oxidation of organic precursors, or these acids are produced together with ozone in daytime. The low correlation coefficients of ozone and oxalic and other diacids in nighttime may suggest that the nighttime chemistry of diacids is mainly initiated with NO 3 radical and other oxidizing agents such as H 2 O 2 (Claeys et al, 2004;Herrmann et al, 2000).…”
Section: Relations Of Diacids With Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…These results support that oxalic, malonic, and succinic acids as well as phthalic and glyoxylic acids are produced by the photochemical oxidation of organic precursors, or these acids are produced together with ozone in daytime. The low correlation coefficients of ozone and oxalic and other diacids in nighttime may suggest that the nighttime chemistry of diacids is mainly initiated with NO 3 radical and other oxidizing agents such as H 2 O 2 (Claeys et al, 2004;Herrmann et al, 2000).…”
Section: Relations Of Diacids With Ozonementioning
confidence: 99%
“…The higher ratios of C 2 /total diacids in nighttime indicate that organic aerosols are more enriched with oxalic acid by chemical processing at night. Some laboratory studies demonstrated that aqueous phase reactions to produce C 2 could be mainly initiated in nighttime by NO 3 (Herrmann et al, 2000) and H 2 O 2 (in the presence of H 2 SO 4 ) (Claeys et al, 2004), although NO 3 reactions are usually slow. Because the nighttime RH increased significantly (up to 100%, on average 78%), C 2 could be produced in aqueous phase in nighttime.…”
Section: Possible Production Of Oxalic Acid In Nighttimementioning
confidence: 99%
“…The acetic acid adduct ions for the hydroxynitrates and the nitrooxyhydroxyperoxides are formed owing to the presence of acetic acid in the UPLC mobile phase. Previous studies have shown that non-acidic hydroxylated species (such as the 2-methyltetrols) and organic peroxides formed from the photooxidation of isoprene (Claeys et al, 2004;Edney et al, 2005;Surratt et al, 2006) are either undetectable or yield weak negative ions when using (-)ESI-MS techniques. However, it appears that the co-presence of nitrooxy groups in the hydroxylated SOA components allow for these compounds to become acidic enough to be detected by the UPLC/(-)ESI-TOFMS technique, or allow for adduction with acetic acid.…”
Section: Offline Chemical Analysismentioning
confidence: 99%
“…Owing to its high concentration and reactivity with OH radicals, isoprene plays an important role in the photochemistry occurring within the atmospheric boundary layer. Recently, it has been shown that the photooxidation of isoprene leads to the formation of low volatility species that condense to form SOA (Claeys et al, 2004;Edney et al, 2005;Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Surratt et al, 2006); SOA yields as high as ∼3% have been observed (Kroll et al, 2005;Kroll et al, 2006). Global SOA production from isoprene photooxidation has been estimated to be about 13 Tg yr −1 (Henze et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Isoprene is formed from dimethylallyl-PP and its emission from leaves can significantly influence the surrounding atmosphere. Claeys et al (2004) showed that photo-oxidation of isoprene emitted from plants in the Amazon was sufficient to influence the rain regime in the region. Additionally, isoprene emission has been reported to protect plants against high temperatures particularly during rapid temperature fluctuation periods (Velikova and Loreto, 2005).…”
mentioning
confidence: 99%